2014
DOI: 10.3892/or.2014.3381
|View full text |Cite
|
Sign up to set email alerts
|

KPNA2 is a promising biomarker candidate for esophageal squamous cell carcinoma and correlates with cell proliferation

Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the most lethal malignant cancers worldwide, with a poor 5-year prognosis. Karyopherin α 2 (KPNA2) is a nuclear membrane protein that mediates nucleus-to-cytoplasm shuttling. Its expression is elevated in multiple forms of cancer, and it can be secreted into the serum. However, the concentration of KPNA2 in serum from ESCC patients and the role of KPNA2 in ESCC cells remains unclear. The aim of the present study was to determine the concentration of KPNA2 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 31 publications
3
23
1
Order By: Relevance
“…Existing evidences have shown that KPNA2 was over-expressed in multiple malignancies [911]. Meanwhile, it has been suggest that elevated KPNA2 could be associated with poor prognosis in a variety of solid tumors, including colorectal cancer [1113], breast cancer [1417], gastric cancer [10, 18, 19] and hepatocellular carcinoma [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Existing evidences have shown that KPNA2 was over-expressed in multiple malignancies [911]. Meanwhile, it has been suggest that elevated KPNA2 could be associated with poor prognosis in a variety of solid tumors, including colorectal cancer [1113], breast cancer [1417], gastric cancer [10, 18, 19] and hepatocellular carcinoma [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Karyopherin-α2 (KPNA2), a member of the importin family, is a kind of nuclear transport proteins [8]. One of the last major steps of the most intracellular signaling pathways is nucleocytoplasmic transport [9].…”
Section: Introductionmentioning
confidence: 99%
“…Karyopherin alpha 2 (KPNA2), which also known as importin α1, belongs to the karyopherin family; it delivers numerous cargo proteins to the nucleus and is then translocated back into the cytoplasmic compartments in a Ran‐GTP‐dependent manner . Aberrant KPNA2 expression has been observed in various human cancers, including lung cancer, breast cancer, melanoma, cervical cancer, esophageal SCC, ovarian cancer, prostate cancer, liver cancer, bladder cancer, brain cancer, gastric cancer, upper tract urothelial carcinoma, cholangiocarcinoma, and colorectal cancer . The KPNA2 overexpression is associated with tumor invasiveness and a poor prognosis in several malignancies .…”
Section: Introductionmentioning
confidence: 99%
“…The KPNA2 overexpression is associated with tumor invasiveness and a poor prognosis in several malignancies . Notably, it has been shown that KPNA2 can be secreted by cancer cells, and higher KPNA2 levels have been detected in the serum samples of patients with lung, ovarian, and colorectal cancer compared with those in healthy controls . However, the clinical and biological significance of KPNA2 in oral cavity SCC has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation